Pearl seed inserting method for pearl culture in fresh water mussel - SHAOHE XIE (2004)
本发明先将细胞小片紧贴在珠核上，然后用无创送核器将贴有细胞小片的珠核送入河蚌的外套膜或者内脏囊中核位上。所述的细胞小片位于珠核的前面。本发明由于采用了无创送核器将核片同送的插核法，使原本用二个动作才能完成一个插核位置的作业，变为用一个动作就可完成，手术作业方便、快捷，提高了手术的成功率。留核率、成珠率高，经济价值高、应用本发明，插核育珠留核率在80％以上，成珠率高达90％以上，经济价值比普通无核珍珠的经济价值提高十倍以上。 After cell die, which is before the pearl seed, is stuck closely to pearl seed, the pearl seed is planted with seed feeder into pallium or internal organ bag or fresh water mussel. The method of planting cell die and pearl seed simultaneously is convenient, fast and high in efficiency. The present invention can result in high seed retaining rate, high pearl producing efficiency, and high economicbenefits.